Evaluation the Levels of Thyroid Hormones among Iraqi Pregnant Women - Zahraa Safaa Al-deen Musa (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study was carried out to evaluate the levels of thyroid hormones among pregnant Iraqi women according to the age.. The study group comprised of (140)of full term pregnant women scheduled follows up the alterations of thyroid hormones, the control group included (50)of healthy women volunteers. Serum concentrations levels of T3, T4 and (TSH) were estimated using (ELFA) technique. In the study groups, blood samples were obtained from various ages pregnant women . Range age of the study groups was (20-40) years. In the control group: serum T3 andT4 levels were decreased slightly with increasing age respectively, while TSH levels were increased slightly with increasing age without significant difference P>0.05 and the values were within the normal range. In the hyperthyroidism which included (45) patients women , there were continuously higher in concentration levels of T3, and T4 than that in the control group, but TSH concentration decreased with highly a significant difference P<0.01.While, in hypothyroidism which included (45) patient women ,the concentrations of T3 and T4 were lower than that in the control group, but TSH increased with a highly significant difference P<0.05.